Magic coverings and the Kronecker product - López S.C.; Muntaner-Batle F.A.; Rius-Font M. (Utilitas Mathematica, 2014)
In this paper we study a relationship existing among (super) magic coverings and the well known Kronecker product of matrices. We also introduce the concept of ℤn-property for digraphs in order to study this relation mentioned before. The results obtained in this paper can also be applied to construct S-magic partitions.